Ethnography and PRA among Gambian traditional birth attendants: a methods discussion - Nyanzi, Stella; Bah, Ousman; Joof, Sulayman; Walraven, Gijs (Qualitative Research, 2007)
Ethnographers are often sceptical of employing Participatory Rapid Appraisal (PRA) tools in their research, calling them ‘a quick and dirty’ approach. However, ethnography has limitations as a research method. We therefore combined the two methods to enhance their strengths. Based on fieldwork in rural Gambia, this article discusses the procedure, merits and shortcomings of triangulating PRA and conventional ethnography methods to conduct research among an illiterate study population of traditional birth attendants. When tailored to suit the target study population, some PRA tools do enhance the emic perspective – thus empowering the study participants and making research results more context-relevant.
Keywords: birth attendants; ethnography; methodology; participatory rapid appraisal; triangulation